SOLUSI PREVENTIF HADIS TERHADAP FENOMENA PERUNDUNGAN - Pulungan, Nur Hamidah; Barus, Muhammad Irsan; Nasution, Zulhija Yanti (IAIN Syekh Nurjati Cirebon, 2023)
Bullying has become a significant social problem due to frequent misunderstandings and has negative impacts on both the perpetrators and the victims in the form of intimidation, verbal/physical abuse or discriminatory actions. This research aims to explore the preventive solutions offered by hadith in addressing bullying. The major research includes the classification of relevant hadith literature using the HadistSoft digital application, while the minor research involves the analysis of ḥadīth that provides preventive solutions to bullying. The research locus is the general public. The purpose of this study is to identify and articulate the teachings of hadith that can be applied as preventive measures against bullying. This research adopts a qualitative approach using descriptive-analytical methods in a library research type. The results show that hadith offers various preventive solutions that can be applied to reduce and prevent bullying, such as emphasizing spiritual advice, fostering cooperation to eliminate conflicts, and removing the inferiority complex of bullying victims. These solutions are expected to be integrated into educational programs and school policies to create a safer and more harmonious environment.Perundungan telah menjadi masalah sosial yang memiliki dampak negatif bagi pelaku dan korban dalam bentuk intimidasi, pelecehan verbal/fisik ataupun tindakan diskriminatif. Penelitian ini bertujuan untuk mengidentifikasi ajaran-ajaran hadis yang dapat diterapkan sebagai langkah preventif terhadap perundungan. Penelitian ini menggunakan metode kualitatif deskriptif-analitis dengan pendekatan studi kepustakaan. Hasil penelitian menunjukkan bahwa hadis menawarkan berbagai solusi preventif yang dapat diterapkan untuk mengurangi dan mencegah perundungan, seperti penekanan pada pemberian nasihat spiritual, menjalin kerjasama untuk menghilangkan konflik dan menghilangkan sikap inferior bagi korban perundungan. Solusi ini diharapkan dapat diintegrasikan dalam program pendidikan dan kebijakan sekolah untuk menciptakan lingkungan yang lebih aman dan harmonis.